2012
DOI: 10.1371/journal.pone.0051264
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteogenic Differentiation of Adipose Derived Stem Cells by Microstructured Nitinol Actuator-Mediated Mechanical Stress

Abstract: The development of large tissue engineered bone remains a challenge in vitro, therefore the use of hybrid-implants might offer a bridge between tissue engineering and dense metal or ceramic implants. Especially the combination of the pseudoelastic implant material Nitinol (NiTi) with adipose derived stem cells (ASCs) opens new opportunities, as ASCs are able to differentiate osteogenically and therefore enhance osseointegration of implants. Due to limited knowledge about the effects of NiTi-structures manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…To date, the biophysical induction of hASC differentiation has been reported by several authors but only in the presence of an induction medium, suggesting that mechanical loading might only boost differentiation. Nevertheless, the data from the present study are in line with a recent study demonstrating that mechanical stress alone (mediated by a microstructured nitinol actuator) can induce osteogenic differentiation (Strauß et al ., ). Some authors have reported that in in vivo animal models ESWs activated cell proliferation and bone regeneration of segmental defects (Wang et al ., ) and that the ESW‐promoted healing was achieved by stimulation of mesenchymal stem cell recruitment and differentiation into bone‐forming cells (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…To date, the biophysical induction of hASC differentiation has been reported by several authors but only in the presence of an induction medium, suggesting that mechanical loading might only boost differentiation. Nevertheless, the data from the present study are in line with a recent study demonstrating that mechanical stress alone (mediated by a microstructured nitinol actuator) can induce osteogenic differentiation (Strauß et al ., ). Some authors have reported that in in vivo animal models ESWs activated cell proliferation and bone regeneration of segmental defects (Wang et al ., ) and that the ESW‐promoted healing was achieved by stimulation of mesenchymal stem cell recruitment and differentiation into bone‐forming cells (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These characteristics make NiTi alloys particularly suitable, e.g., as stent material [116118] and scaffolds in bone tissue engineering [119]. Synthesis of NiTi nanoparticles by laser ablation in liquid has been described in the literature [115,120] and these nanoparticles were frequently adsorbed to implant surfaces as nanocoatings [121].…”
Section: Reviewmentioning
confidence: 99%
“…Most studies report that mechanical stress promotes osteogenic differentiation of BMSCs or osteoblasts (14)(15)(16)(17)(18)(19)(20)(21). Mechanical stress might also up-regulate the expression of osteogenic genes of ASC (22)(23)(24)(25). Results from our previous study have shown that cyclic tensile mechanical loading of long duration could promote the expression of BMP-2 and Runx2 and thus, osteogenic differentiation of ASCs in osteogenic medium (26) or adipogenic medium (27).…”
Section: Introductionmentioning
confidence: 99%